Generation of a humanized FXII knock‐in mouse—A powerful model system to test novel anti‐thrombotic agents. (19th August 2021) - Beck, Sarah; Stegner, David; Loroch, Stefan; Baig, Ayesha A.; Göb, Vanessa; Schumbrutzki, Cornelia; Eilers, Eva; Sickmann, Albert; May, Frauke; Nolte, Marc W.; Panousis, Con; Nieswandt, Bernhard
Abstract: Background: Effective inhibition of thrombosis without generating bleeding risks is a major challenge in medicine. Accumulating evidence suggests that this can be achieved by inhibition of coagulation factor XII (FXII), as either its knock‐out or inhibition in animal models efficiently reduced thrombosis without affecting normal hemostasis. Based on these findings, highly specific inhibitors for human FXII(a) are under development. However, currently, in vivo studies on their efficacy and safety are impeded by the lack of an optimized animal model expressing the specific target, that is, human FXII. Objective: The primary objective of this study is to develop and functionally characterize a humanized FXII mouse model. Methods: A humanized FXII mouse model was generated by replacing the murine with the human F12  gene (genetic knock‐in) and tested it in in vitro coagulation assays and in in vivo thrombosis models. Results: These hF12 KI mice were indistinguishable from wild‐type mice in all tested assays of coagulation and platelet function in vitro and in vivo, except for reduced expression levels of hFXII compared to human plasma. Targeting FXII by the anti‐human FXIIa antibody 3F7 increased activated partial thromboplastin time dose‐dependently and protected hF12 KI mice in an arterial thrombosis model without affecting bleeding times. Conclusion: These data establish the newly generated hF12 KI mouse as a powerful and unique model system for in vivo studies on anti‐FXII(a) biologics, supporting the development of efficient and safe human FXII(a) inhibitors.